Allergen and rhinovirus (RV) regulation of PD-L1/PD1 in allergic asthma - Kölle, Julia; Haag, Patricia; Vuorinen, T.; Kiefer, Alexander; Papadopoulos, N. G.; Finotto, Susetta (ALLERGY, 2019)
CRIS-Team WoS Importer:2019-08-27

Anatomical accuracy of abdominal lesion localization: Retrospective automatic rigid image registration between FDG-PET and MRI - Kiefer, Alexander; Kuwert, Torsten; Hahn, Dieter; Hornegger, Joachim; Uder, Michael; Ritt, Philipp (Nuklearmedizin-Nuclear Medicine, 2011)
Software-based image registration can improve the diagnostic value of imaging procedures and is an alternative to hybrid scanners. The aim of this study was to evaluate the anatomical accuracy of automatic rigid image registration of independently acquired datasets of positron emission tomography with F-deoxyglucose and abdominal magnetic resonance imaging. Patients, methods: Analyses were performed on 28 abdominal lesions from 20 patients. The PET data were obtained using a stand-alone PET camera in 14 cases and a hybrid PET/CT scanner in 9 cases. The abdominal T1- and T2-weighted MRI scans were acquired on 1.5 T MRI scanners. The mean time interval between MRI and PET was 7.3 days (0-28 days). Automatic rigid registration was carried out using a self-developed registration tool integrated into commercial available software (InSpace for Siemens Syngo). Distances between the centres of gravity of 28 manually delineated neoplastic lesions represented in PET and MRI were measured in X-, Y-, and Z-direction. The intra- (intraclass correlation 0.94) and inter- (intraclass correlation 0.86) Positronenemissionsobserver repeatability were high. Results: The average distance in all MRI sequences was 5.2 ± 7.6 mm in X-direction, 4. ± 3.7 mm in Y-direction and 6.1 ± 5.1 mm in Z-direction. There was a significantly higher misalignment in Z-direction (p < 0.05). The misalignment was not significantly different for the registration of T1- and T2- weighted sequences (p = 0.7). Conclusion: The misalignment between FDG-PET and abdominal MRI registered using an automated rigid registration tool was comparable to data reported for software-based fusion between PET and CT. Although this imprecision may not affect diagnostic accuracy, it is not sufficient to allow for pixel-wise integration of MRI and PET information. © Schattauer 2011.

Contribution of repeated infections in asthma persistence from preschool to school age: Design and characteristics of the PreDicta cohort - Xepapadaki, Paraskevi; Bachert, Claus; Finotto, Susetta; Jartti, Tuomas; Konstantinou, George N.; Kiefer, Alexander; Kowalski, Marek; Lewandowska-Polak, Anna; Lukkarinen, Heikki; Roumpedaki, Eirini; Sobanska, Anna; Sintobin, Ina; et al. (Pediatric Allergy and Immunology, 2018)
BACKGROUND: The PreDicta cohort was designed to prospectively evaluate wheeze/asthma persistence in preschoolers in association with viral/microbial exposures and immunological responses. We present the cohort design and demographic/disease characteristics and evaluate unsupervised and predefined phenotypic subgroups at inclusion. METHODS: PreDicta is a 2-year prospective study conducted in five European regions, including children 4-6 years with a diagnosis of asthma as cases and healthy age-matched controls. At baseline, detailed information on demographics, asthma and allergy-related disease activity, exposures, and lifestyle were recorded. Lung function, airway inflammation, and immune responses were also assessed. Power analysis confirmed that the cohort is adequate to answer the initial hypothesis. RESULTS: A total of 167 asthmatic children (102 males) and 66 healthy controls (30 males) were included. Groups were homogeneous in respect to most baseline characteristics, with the exception of male gender in cases (61%) and exposure to tobacco smoke. Comorbidities and number and duration of infections were significantly higher in asthmatics than controls. 55.7% of asthmatic children had at least one positive skin prick test to aeroallergens (controls: 33.3%, P = .002). Spirometric and exhaled nitric oxide values were within normal limits; only baseline FEV0.5 and FEV1 reversibility values were significantly different between groups. Viral infections were the most common triggers (89.2%) independent of severity, control, or atopy; however, overlapping phenotypes were also common. Severity and control clustered together in an unsupervised analysis, separating moderate from mild disease. CONCLUSIONS: The PreDicta cohort presented no differences in non-asthma related measures; however, it is well balanced regarding key phenotypic characteristics representative of "preschool asthma".
EVALuna2:52975

CTLA4 induction by Rhinovirus (RV) in pediatric asthma - Kölle, Julia; Haag, Patricia; Vuorinen, T.; Kiefer, Alexander; Zimmermann, Theodor; Papadopoulos, N. G.; Finotto, Susetta (2018)
EVALuna2:34821

Dual-source computed tomography of the lung with spectral shaping and advanced iterative reconstruction: potential for maximum radiation dose reduction - Wetzl, Matthias; May, Matthias; Weinmann, Daniel; Hammon, Matthias; Treutlein, Christoph; Zeilinger, Martin; Kiefer, Alexander; Trollmann, Regina; Wölfle, Joachim; Uder, Michael; Rompel, Oliver (Pediatric Radiology, 2020)
Background: Radiation dose at CT should be as low as possible without compromising diagnostic quality. Objective: To assess the potential for maximum dose reduction of pediatric lung dual-source CT with spectral shaping and advanced iterative reconstruction (ADMIRE). Materials and methods: We retrospectively analyzed dual-source CT acquisitions in a full-dose group (FD: 100 kV, 64 reference mAs) and in three groups with spectral shaping and differing reference mAs values (Sn: 100 kV, 96/64/32 reference mAs), each group consisting of 16 patients (age mean 11.5 years, standard deviation 4.8 years, median 12.8 years, range 1.3–18 years). Advanced iterative reconstruction of images was performed with different strengths (FD: ADMIRE Level 2; Sn: ADMIRE Levels 2, 3 and 4). We analyzed dose parameters and measured noise. Diagnostic confidence and detectability of lung lesions as well as anatomical structures were assessed using a Likert scale (from 1 [unacceptable] to 4 [fully acceptable]). Results: Compared to full dose, effective dose was reduced to 16.7% in the Sn 96 group, 11.1% in Sn64, and 5.5% in Sn32 (P<0.001). Noise values of Sn64ADM4 did not statistically differ from those in FDADM2 (45.7 vs. 38.9 Hounsfield units [HU]; P=0.132), whereas noise was significantly higher in Sn32ADM4 compared to Sn64ADM4 (61.5 HU; P<0.001). A Likert score >3 was reached in Sn64ADM4 regarding diagnostic confidence (3.2) and detectability of lung lesions (3.3). For detectability of most anatomical structures, no significant differences were found between FDAM2 and Sn64ADM4 (P≥0.05). Conclusion: In pediatric lung dual-source CT, spectral shaping together with ADMIRE 4 enable radiation dose reduction to about 10% of a full-dose protocol while maintaining an acceptable diagnostic quality.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Adolescents; Advanced iterative reconstruction; Children; Dual-source computed tomography; Lung; Radiation dose reduction; Spectral shaping; Tin prefiltration

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma - Bergauer, Annika; Sopel, Nina; Kross, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2016)
We analysed the influence of rhinovirus (RV) in nasopharyngeal fluid (NPF) on type I and III interferon (IFN) responses (e.g. IFN-? and IFN -: ?) and their signal transduction, at baseline and during disease exacerbation, in cohorts of pre-school children with and without asthma.At the time of recruitment into the Europe-wide study PreDicta, and during symptoms, NPF was collected and the local RV colonisation was analysed. Peripheral blood mononuclear cells (PBMCs) were challenged in vitro with RV or not. RNA was analysed by quantitative real-time PCR and gene arrays. Serum was analysed with ELISA for IFNs and C-reactive protein.We found that PBMCs from asthmatic children infected in vitro with the RV1b serotype upregulated MYD88, IRF1, STAT1 and STAT2 mRNA, whereas MYD88, IRF1, STAT1 and IRF9 were predominantly induced in control children. Moreover, during symptomatic visits because of disease exacerbation associated with RV detection in NPF, IFN-? production was found increased, while IFN-? secretion was already induced by RV in asthmatic children at baseline.During asthma exacerbations associated with RV, asthmatic children can induce IFN-? secretion, indicating a hyperactive immune response to repeated respiratory virus infection.
EVALuna2:9365

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma - Bergauer, Annika; Sopel, Nina; Kross, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2017)
EVALuna:34061

IL-33/ST2 immune responses to respiratory bacteria in pediatric asthma - Hentschke, Isabell; Graser, Anna; Melichar, Volker O.; Kiefer, Alexander; Zimmermann, Theodor; Kross, Bettina; Haag, Patricia; Xepapadaki, Paraskevi; Papadopoulos, Nikolaos G.; Bogdan, Christian; Finotto, Susetta (Scientific Reports, 2017)
Here we investigated the relationship between local bacterial colonization and anti-bacterial immune responses in pre-school asthmatic and control children within the EU-wide study PreDicta. In this cohort of pre-school asthmatic children, nasopharyngeal colonization with Gram-negative bacteria such as Haemophilus influenzae and Moraxella catarrhalis was found to be associated with the highest interferon beta (IFN?) and IL-33 levels in the nasal pharyngeal fluids (NPF). IL33R-ST2 was found induced in the blood of asthmatic children with additional Gram + bacteria in the nasopharynx (Gr+/-). Furthermore, asthmatic children had more episodes of infection that required antibiotic therapy than the control group. Treatment with antibiotics associated with reduced ST2 in blood cells of both asthmatic and control children and reduced IL-33 levels in the airways of asthmatic children. In the absence of Staphylococcus (S.) aureus in NPF, antibiotic therapy associated with decreased IL-33 levels in the NPF and lower ST2 values in the blood of control children but not of asthmatic children. These data suggest that, in asthmatic children, Gram- bacteria, which persist after antibiotic therapy, contributes to IL-33 locally and associated with Gr + bacteria colonization in the airways, inhibited IFN-? and in the absence of Staphylococcus (S.) aureus, induced ST2 bearing cells in their blood.
EVALuna2:7728

ILC2 Lung-Homing in Cystic Fibrosis Patients: Functional Involvement of CCR6 and Impact on Respiratory Failure - Schulz-Kuhnt, Anja; Greif, Vicky; Hildner, Kai; Knipfer, Lisa; Döbrönti, Michael; Zirlik, Sabine; Fuchs, Florian; Atreya, Raja; Zundler, Sebastian; Lopez Posadas, Rocío; Neufert, Clemens; Ramming, Andreas; et al. (Frontiers in Immunology, 2020)
Cystic fibrosis patients suffer from a progressive, often fatal lung disease, which is based on a complex interplay between chronic infections, locally accumulating immune cells and pulmonary tissue remodeling. Although group-2 innate lymphoid cells (ILC2s) act as crucial initiators of lung inflammation, our understanding of their involvement in the pathogenesis of cystic fibrosis remains incomplete. Here we report a marked decrease of circulating CCR6+ ILC2s in the blood of cystic fibrosis patients, which significantly correlated with high disease severity and advanced pulmonary failure, strongly implicating increased ILC2 homing from the peripheral blood to the chronically inflamed lung tissue in cystic fibrosis patients. On a functional level, the CCR6 ligand CCL20 was identified as potent promoter of lung-directed ILC2 migration upon inflammatory conditions in vitro and in vivo using a new humanized mouse model with light-sheet fluorescence microscopic visualization of lung-accumulated human ILC2s. In the lung, blood-derived human ILC2s were able to augment local eosinophil and neutrophil accumulation and induced a marked upregulation of pulmonary type-VI collagen expression. Studies in primary human lung fibroblasts additionally revealed ILC2-derived IL-4 and IL-13 as important mediators of this type-VI collagen-inducing effect. Taken together, the here acquired results suggest that pathologically increased CCL20 levels in cystic fibrosis airways induce CCR6-mediated lung homing of circulating human ILC2s. Subsequent ILC2 activation then triggers local production of type-VI collagen and might thereby drive extracellular matrix remodeling potentially influencing pulmonary tissue destruction in cystic fibrosis patients. Thus, modulating the lung homing capacity of circulating ILC2s and their local effector functions opens new therapeutic avenues for cystic fibrosis treatment.
CRIS-Team Scopus Importer:2020-06-02
Keywords: CCR6; cystic fibrosis; group-2 innate lymphoid cells; tissue remodeling; type-VI collagen

Rhinovirus species/genotypes and interferon-λ: subtypes, receptor and polymorphisms - missing pieces of the puzzle of childhood asthma? - Bergauer, Annika; Sopel, Nina; Kro, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2017)
EVALuna2:25986

Role of TGF-β in anti-rhinovirus immune responses in asthmatic patients - Bielor, Carina; Sopel, Nina; Maier, Anja; Blau, Ashley; Sharma, Himanshu; Vuorinen, Tytti; Kross, Bettina; Mittler, Susanne; Graser, Anna; Mousset, Stephanie; Melichar, Volker O.; Kiefer, Alexander; et al. (Journal of Allergy and Clinical Immunology, 2017)
EVALuna2:32796

Successful eradication of newly acquired MRSA in six of seven patients with cystic fibrosis applying a short-term local and systemic antibiotic scheme - Kiefer, Alexander; Bogdan, Christian; Melichar, Volker O. (BMC Pulmonary Medicine, 2018)
BACKGROUND: In individuals with cystic fibrosis (CF), colonization with methicillin-resistant Staphylococcus aureus (MRSA) was reported to be associated with a deterioration of pulmonary disease as reflected by an accelerated decline in lung function. Thus, an early eradication of MRSA could be beneficial in these patients. Here, we report on an intensified MRSA eradication protocol. METHODS: Since 2012 a protocol for the eradication of newly acquired MRSA has been used in our CF Clinic, combining oral rifampicin and fusidic acid, inhaled vancomycin, nasal mupirocin, local antiseptic treatment and hygienic directives all of which are applied for only 7 days during an inpatient hospital stay. RESULTS: Since 2012 seven patients (3 male, 4 female; age range 4 to 30 years) newly acquired MRSA. In 6 of the 7 patients (86%) successful eradication of MRSA was achieved upon first treatment using the protocol described above. In one patient a second course of treatment was performed which, however, also failed to eliminate the colonizing MRSA. CONCLUSIONS: Our protocol led to an eradication rate of 86%. The impact of each individual component of the protocol remains to be determined.
EVALuna2:33304

Targeted deletion of NFAT-Interacting-Protein-(NIP) 45 resolves experimental asthma by inhibiting Innate Lymphoid Cells group 2 (ILC2) - Koch, Sonja; Knipfer, Lisa; Kölle, Julia; Mirzakhani, Hooman; Graser, Anna; Zimmermann, Theodor; Kiefer, Alexander; Melichar, Volker O.; Rascher, Wolfgang; Papadopoulos, Nikolaos G.; Rieker, Ralf; Raby, Benjamin A.; et al. (Scientific Reports, 2019)
Here we investigated the role of NFAT-interacting protein (NIP)-45, an Interleukin (IL)-4 inducing Transcription Factor, and its impact on the differentiation of Group 2 Innate -Lymphoid -Cells (ILC2s) in the pathogenesis of asthma. NIP45, a transcription factor regulating NFATc1 activity, mRNA was found to be induced in the Peripheral Blood mononuclear cells (PMBCs) of asthmatic pre-school children with allergies and in the peripheral blood CD4+ T cells from adult asthmatic patients. In PBMCs of asthmatic and control children, NIP45 mRNA directly correlated with NFATc1 but not with T-bet. Targeted deletion of NIP45 in mice resulted in a protective phenotype in experimental asthma with reduced airway mucus production, airway hyperresponsiveness and eosinophils. This phenotype was reversed by intranasal delivery of recombinant r-IL-33. Consistently, ILC2s and not GATA3+ CD4+ T-cells were decreased in the lungs of asthmatic NIP45−/− mice. Reduced cell number spleen ILC2s could be differentiated from NIP45−/− as compared to wild-type mice after in vivo injection of a microcircle-DNA vector expressing IL-25 and decreased cytokines and ILC2 markers in ILC2 differentiated from the bone marrow of NIP45−/− mice. NIP45 thus emerges as a new therapeutic target for the resolution of the airway pathology, down-regulation of ILC2s and mucus production in asthma.
CRIS-Team Scopus Importer:2019-11-08

Tgf-beta regulation and regulated anti-rhinovirus (RV) immune responses in asthma - Finotto, Susetta; Bielor, Carina; Sopel, Nina; Vuorinen, T.; Melichar, V. O.; Kiefer, Alexander; Zimmermann, Theodor; Papadopoulos, N. G.; Weiss, S. T. (2017)
EVALuna2:33023

Type 1 interferon alpha (IFN-a) regulation by respiratory viruses in pediatric asthma - Finotto, Susetta; Bergauer, Annika; Sopel, Nina; Kross, B.; Vuorinen, T.; Weiss, S. T.; Rauh, Manfred; Melichar, V. O.; Kiefer, Alexander; Zimmermann, Theodor; Ml, Kowalski; Jartti, T.; et al. (2017)
EVALuna2:33022